Self-Esteem, Parental Social Support, and Academic Achievement among Junior High School Students in Public Schools - Indah Purnama Sari; Yuzarion Yuzarion (Universitas PGRI SUMATERA BARAT, 2025)
This study aims to examine the relationship between self-esteem, parental social support, and students’ academic achievement in public junior high schools. A quantitative research design was employed, utilizing two primary instruments: the Self-Esteem Scale and the Parental Social Support Scale. Additionally, academic achievement data were obtained from the Academic Student Transcript System (ASTS) for the 2023/2024 academic year, focusing on eighth-grade students. The target population comprised 212 students, from which a sample of 113 was selected through cluster random sampling. Data analysis was conducted using multiple linear regression via SPSS version 19.00 for Windows. The results of the main hypothesis test indicated a multiple correlation coefficient (R) of 0.420, an F-value of 11.799, and a significance level of 0.000 (p < 0.01), suggesting a statistically significant relationship between the independent variables and academic achievement. The first minor hypothesis showed a regression coefficient of 0.203 with a significance level of 0.032 (p < 0.05), indicating a positive and significant relationship between self-esteem and academic achievement. The second minor hypothesis revealed a partial correlation coefficient of 0.312 with a significance level of 0.001 (p < 0.01), indicating a strong and statistically significant relationship between parental social support and academic achievement. Overall, self-esteem and parental social support jointly contributed 17.65% to the variance in students’ academic achievement. These findings underscore the importance of both psychological and social factors in supporting students’ academic success. Keywords: Academic achievement, parental social support, self-esteem.